Ibn Khaldun's Concept of Law and its Relevance in the Formation of Modern Legal Systems - Hasan, Ahmadi; Muzainah, Gusti; ., Jalaluddin; al Amruzi, Fahmi; Hafidzi, Anwar; ., Bahran; ., Nadiyah (KnE Social Sciences, 2023)
This article discussed the concept of law in Ibn Khaldun’s thoughts and its relevance in forming modern legal systems. This research used qualitative research methods with data collection techniques through a literature review of Ibn Khaldun’s works and several other relevant sources. The main focus of the research analysis was the concepts of al-’adl law, inheritance law, and justice in law. The results showed that Ibn Khaldun’s thoughts on al-’adl law, inheritance law, and justice in law were highly relevant to forming modern legal systems. The concept of al-’adl law taught that law should be enforced fairly, while the concept of inheritance law provided the basis for developing family law. In addition, Ibn Khaldun’s concept of justice in law had significant implications for the fair and equal enforcement of the law. In conclusion, Ibn Khaldun’s thoughts on law can contribute to forming modern legal systems and new and alternative perspectives for the development of law today. Keywords: kwd